Radical-driven degradation mechanism of Cu(II)-EDTA during supercritical water gasification: Insights from ReaxFF molecular dynamics - Tingting Dai; Xiaoxia Guo; Ruochen Xiong; Weiqiang Liu; Weilong Yin; Weichong Deng; Wenwen Wei; Shi Liu; Wen Cao (Journal of Environmental Chemical Engineering, 2026)

Upcycling municipal sludge into upgraded phosphate via low-temperature catalytic oxidation and acid-base washing - Yang Yang; Xingang Wang; Xuandi Cao; Zheqin Dai; Ruochen Wang; Hongliang Dai (Journal of Environmental Chemical Engineering, 2026)

Multi-objective optimization of rice production and environmental sustainability under climate change in the Yangtze River Delta: A DNDC-random forest framework approach - Shuoshuo Liang; Ping He; Qingnan Chu; Wentian He; Ruochen Li; Xinpeng Xu; Rong Jiang; Shuang Liu; Linkui Cao; Zhimin Sha (Field Crops Research, 2026)

Biochemically induced phosphate precipitation in enhanced biological phosphorus removal system: Mechanism, application and future directions - Shipeng Li; Xiaoli Zhou; Xuandi Cao; Ruochen Wang; Zheqin Dai; Haq Nawaz Abbasi; Guangcan Zhu; Hongya Geng; Xingang Wang; Hongliang Dai (Water Research, 2026)

Advancements and Future Perspectives in Biological Nitrogen and Phosphorus Removal Coupled Resource Recovery Processes - Deyi Jiang; Haoyun Wang; Xuandi Cao; Ruochen Wang; Zheqin Dai; Wuxiang Zhang; Haq Nawaz Abbasi; Bing Li; Xingang Wang; Hongliang Dai (Water, Air, & Soil Pollution, 2025)

An integrated process of nitritation-anammox and vivianite crystallization for pollutant removal and resource recovery - Deyi Jiang; Hongliang Dai; Haoyun Wang; Xuandi Cao; Ruochen Wang; Zheqin Dai; Bing Li; Haq Nawaz Abbasi; Hongya Geng; Guangcan Zhu; Xingang Wang (Journal of Environmental Chemical Engineering, 2025)

Screening, identification, and application of anaerobic ammonia oxidizing bacteria in activated sludge systems: A comprehensive review - Haoyun Wang; Hongliang Dai; Deyi Jiang; Xuandi Cao; Ruochen Wang; Zheqin Dai; Wuxiang Zhang; Haq Nawaz Abbasi; Bing Li; Guangcan Zhu; Xingang Wang (Journal of Environmental Management, 2025)

Global mapping of forest clumping index based on GEDI canopy height and complementary data - Xingmin Zhao; Jing M. Chen; Yongguang Zhang; Ziti Jiao; Liangyun Liu; Feng Qiu; Jinlong Zang; Ruochen Cao (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Structural analysis of petroleum acids in highly acidic crude oil and deacidification using organic amines - Ruochen Ma; Lingli Jia; Hongyu Zhang; Fahai Cao; Jianhui Shao; Junjie Zhang; Shuiliang Yan; Jun Xu (Fuel, 2024)

Effect of Fenton pre-oxidation on the physicochemical properties of sludge-based biochar and its adsorption mechanisms for ammonia nitrogen removal - Jun Cao; Ruochen Wang; Hualun Zhu; Songshan Cao; Zhipeng Duan (Journal of Environmental Chemical Engineering, 2023)

Integration of pre-precipitation optimizing performance of culture medium prepared from salvaged cyanobacterial slurry - Ruochen Wang; Jun Cao; Wei Zhu; Yi Lv (Chemosphere, 2023)

The increasing contribution of greening to the terrestrial evapotranspiration in China - Genan Wu; Xinchen Lu; Wei Zhao; Ruochen Cao; Wenqi Xie; Liyun Wang; Qiuhong Wang; Jiexuan Song; Shaobo Gao; Shenggong Li; Zhongmin Hu (Ecological Modelling, 2023)

An overall consistent increase of global aridity in 1970–2018 - Dengnan Luo; Zhongmin Hu; Licong Dai; Guolong Hou; Kai Di; Minqi Liang; Ruochen Cao; Xiang Zeng (Journal of Geographical Sciences, 2023)

The global decline in the sensitivity of vegetation productivity to precipitation from 2001 to 2018 - Xiang Zeng; Zhongmin Hu; Anping Chen; Wenping Yuan; Guolong Hou; Daorui Han; Minqi Liang; Kai Di; Ruochen Cao; Dengnan Luo (Global Change Biology, 2022)
The sensitivity of vegetation productivity to precipitation ( S ppt ) is a key metric for understanding the variations in vegetation productivity under changing precipitation and predicting future changes in ecosystem functions. However, a comprehensive assessment of S ppt over all the global land is lacking. Here, we investigated spatial patterns and temporal changes of S ppt across the global land from 2001 to 2018 with multiple streams of satellite observations. We found consistent spatial patterns of S ppt with different satellite products: S ppt was highest in dry regions while low in humid regions. Grassland and shrubland showed the highest S ppt , and evergreen needle‐leaf forest and wetland showed the lowest. Temporally, S ppt showed a generally declining trend over the past two decades ( p S ppt was especially noticeable in North America and Europe, likely due to the increase in precipitation. In central Russia and Australia, however, S ppt showed an increasing trend. Biome‐wise, most ecosystem types exhibited significant decrease in S ppt , while grassland, evergreen broadleaf forest, and mixed forest showed slight increases or non‐significant changes in S ppt . Our finding of the overall decline in S ppt implies a potential stabilization mechanism for ecosystem productivity under climate change. However, the revealed S ppt increase for some regions and ecosystem types, in particular global grasslands, suggests that grasslands might be increasingly vulnerable to climatic variability with continuing global climate change.